Developing Problem Based Learning supplemental materials to increase 7th graders higher-order thinking skills - Miftiani, Sausallina Widad; Rochmad, Rochmad; Kharis, Muhammad (Department of Mathematics, Universitas Negeri Semarang, 2020)
The study developed Problem Based Learning supplemental materials and aimed to (1) determine the characteristics of the supplemental materials, (2) determine the validity and readability of the supplemental materials, and (3) analyze the increase of Higher Order Thinking Skills after using the supplemental materials in the classroom. The method used in this research is research and development with 3D models (define, design, and develop). The increase of Higher Order Thinking Skills was analyzed by comparing the learning outcomes of the class that used the supplemental materials and class that used the default materials provided by schools. The population in this study were six classes of 7th grade of a Junior High School in Ungaran. The samples were selected by a random sampling technique to find a class for the experimental class and another class as a control class. Data were analyzed using a t-test and gain test. The study concluded that using Problem Based Learning supplemental material increased the Higher Order Thinking Skills of students.